The training of tempeh yoghurt and tempeh brownies production as an effort to increase the sell-ing value of tempeh in the somber small industrial estate, Balikpapan - Alfonsina Abat Amelenan Torimtubun; Linda Kirana Singagerda; Lusi Ernawati (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Tempeh is an Indonesian traditional food processed by soybean fermentation by Rhizopus oligosporus mold which is inexpensive, has the distinctive flavour and high nutritional value. High protein tempeh has been accepted as a healthy food. However, tempeh is still associated with low socioeconomic class food. Therefore, it is necessary to look for an alternative tempeh processing to increase its economic value by processing tempeh into yoghurt and brownies. The aim of this community service is to increase the community knowledge about the diversification of tempeh processed products in general and in particular to provide a training about the processing of tempeh juice into yoghurt and tempeh pulp into brownies in order to help the increasing economic value of tempeh production from Somber small industrial centre in Balikpapan. Methods used are gradually from: (1) initial preparation in the form of a location survey and a socialization team formation, (2) training preparation in the form of yoghurt tempeh and brownies tempeh production as a tester, banners and brochures printing, and tempeh production process documentation for presentation material of training socialization, (3) implementation of training, up to (4) evaluation of results in the form of product organoleptic survey. The results of organoleptic test showed that yoghurt and brownies from juice and tempeh pulp were accepted and preferred by Somber small industrial centre community as panellists with a rating score of colour, aroma, texture and taste are 1.6; 1,2; 1,2; 0.8 for tempeh yoghurt and 2.6; 2.2; 2.2; 2.8 for tempeh brownies, respectively. Through this program, the tempeh production from Somber can be increased and processed into innovative products that have a higher selling value. Economic analysis and feasibility study is needed to keep this activity run continuously.